(untitled) (Proceedings of Southern Federal University. Philology, 2019)
Nikolay V. Belenov (Samara, Russian Federation) The article introduces and analyzes the Moksha-Mordvinian toponymy of the Samara Luka, which is the area of the modern settlement of the Mordovian population of the Peninsula, that is, toponymic area of settlements Bahilovo, Tornovoe, Shelehmet and of the settlement of Bahilova Polyana. The study was carried out on the basis of topographic and archaeological descriptions of the Samara Luka XVIII – XIX centuries and field materials of the author – both in this area and with the involvement of field own materials from other areas of the Samara Volga region, inhabited by Mordvins. Etymologization of place names is carried out taking into account the characteristic features of Moksha-Mordovian dialects of Samara Luka, local toponymic traditions, as well as a kind of geographical vocabulary that exists in these dialects. On the basis of the analysis of historical Moksha-Mordovian toponymy of Samara Bend, it is concluded that the wider area of settlement of the Mordovian population on the Peninsula in the period of XVI-XVIII centuries. Key words: toponymy, geographic vocabulary, Mordovians, MokshaMordvin dialects, Samarskaya Luka. DOI 10.23683/1995-0640-2019-3-130-137